Effect of Drug Xylazine Hydrochloride in Chemically Immobilizing a Pigmy Elephant under Standing Sedation to Successfully Treat Lameness - a Case Report from Satkosia Gorge Sanctuary, Orissa - Samantray, R. K.; Mishra, A. K. (Indian Forester, 2007)
This paper discusses the treatment of a limping female elephant with left foreleg swelling at carpal joint. This particular female elephant claimed to be a pigmy elephant of Satkosia Gorge Sanctuary, Angul District (Orissa). Because of its leg problem, its movement was restricted and it strayed out from the herd. Specialized treatment was provided during state of standing sedation by tranquilzing through dart firing from a Mod 60-N Dart Gun from a distance of 30-35 m, using the drug Xylazine Hydrochloride. Drugs like long acting antibiotics, analgesics, steroids, neurotonics, liver extract, fluid therapy and other life saving drugs were given on a definite interval i.e. 13.3.2005, 17.3.2005 and 22.3.2005. In each case after the treatment Yuhimbine Hydrochloride was administered intra-veinously for a timely reversal. The swelling of leg was reduced and the mobility was restored. The animal recovered gracefully and as reported it was able to walk properly from 25.3.2005 onwards in the vicinity.